The long non-coding RNA Paupar regulates the expression of both local and distal genes. - Vance, K; Sansom, S; Lee, S; Chalei, V; Kong, L; Cooper, SE; Oliver, P; Ponting, C (2014)
Although some long noncoding RNAs (lncRNAs) have been shown to regulate gene expression in cis, it remains unclear whether lncRNAs can directly regulate transcription in trans by interacting with chromatin genome-wide independently of their sites of synthesis. Here, we describe the genomically local and more distal functions of Paupar, a vertebrate-conserved and central nervous system-expressed lncRNA transcribed from a locus upstream of the gene encoding the PAX6 transcription factor. Knockdown of Paupar disrupts the normal cell cycle profile of neuroblastoma cells and induces neural differentiation. Paupar acts in a transcript-dependent manner both locally, to regulate Pax6, as well as distally by binding and regulating genes on multiple chromosomes, in part through physical association with PAX6 protein. Paupar binding sites are enriched near promoters and can function as transcriptional regulatory elements whose activity is modulated by Paupar transcript levels. Our findings demonstrate that a lncRNA can function in trans at transcriptional regulatory elements distinct from its site of synthesis to control large-scale transcriptional programmes.